PENELUSURAN BEBERAPA FRAGMEN PRASASTI PAÁ¹†Á¸ŒÄ€N DI RUMAH PENDUDUK (DESA PANDANKRAJAN, KECAMATAN KEMLAGI, KABUPATEN MOJOKERTO) - Nugroho, Aang Pambudi (BRIN, 2015)
Not all inscriptions are recovered in a complete condition, several were found only in fragments. One of the inscriptions to have been recovered in a fragmentary condition is the 11th century A.D. Paá¹‡á¸Än inscription issued by King Airlangga.Â This inscription was found in the village of Pandankrajan, Kemlagi Sub-district, Mojokerto Regency. Although the recovery comprises only several fragments, it was of course, formerly complete. It is, therefore, important to analyze the remaining words and sentences that are still visible to try to understand the original meaning of the proclamation.Â